Feel Safe to Take More Risks? Insecure Attachment Increases Consumer Risk-Taking Behavior - Li, Yuanyuan Jamie; Lu, Su; Lan, Junmei; Jiang, Feng (Frontiers in Psychology, 2019)
Attachment styles, originated from early childhood experience, have been documented to influence human behaviors among adults. Drawing on life history theory, we examined whether or not, and how, attachment styles impact risk-taking behaviors beyond evolutionary valid domains, and explored the moderation role of parental status. In the consumer behavior context, three correlational studies provide convergent evidence that insecurely attached (vs. securely attached) consumers are more risk-taking in consumption situations like dining in a toilet-themed restaurant or buying genetically modified products. Specifically, insecurely attached consumers were more likely to take risks in two experiential purchase scenarios (Study 1) and this effect was not domain-specific (Study 2). In Study 3, we showed that safety perception mediated the relationship between attachment insecurity and risk-taking, which was manifested by purchase intentions toward genetically modified products. Specifically, insecurely attached individuals perceived genetically modified products to be safer and were more willing to make a purchase. Additionally, parental status moderates the relationship (Studies 2 and 3). We conclude with a discussion on the implications of attachment theory on consumer risk-taking behaviors from a life history perspective.